Compensation and Honesty: Gender Differences in Lying - Petra Nieken; Simon Dato (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We compare gender differences in lying under two incentive schemes that are widely used in companies: individual performance-pay and tournament incentives. While we do not observe significantly different behavior of males and females given individual performance-pay, females lie significantly less than males if the compensation scheme is switched to tournament incentives. This result is mainly driven by a decrease in the propensity to lie of females in a competitive environment. The gender gap in lying is robust with respect to the gender composition of the pool of opponents. Dishonesty is largest for males competing in a mixed-gender environment.
Keywords: M52; J16; C91; 330